Biophysical characterization of squid’s sucker ring teeth proteins - Kumar Dhawan Akshita (2017)
Sucker ring teeth (SRT) are natural biopolymers entirely composed of proteins (called “suckerins”) exhbiting a block-copolymer-like structure. Despite being stabalized exclusively through the cooperative action of weak interactions, they feature exceptional mechanical properties that rival those of robust engineered polymers. Suckerins share sequence homology to silk and adopt nano-confined β-sheets embedded within an amorphous Gly-rich network. This study combines experimental and computational investigations to identify suckerin protein structure, and bridge it with function/mechanical properties. We illustrate the structural organization of suckerin assembly in processed SRT fibers. We further characterize the structural morphology of the suckerin-19 and its derived construct using different biophysical methods. The conformational propensity of specific sheet-forming domains is predicted using computational modeling and validated using NMR spectroscopy. We elucidate the influence of primary sequence on the β-sheet enriched structures and on the dynamic amorphous domains, to speculate the origin of the mechanical properties.